Misi dalam Gereja Anabaptis Abad XVI: Tinjauan dari Perspektif Paradigma Misi menurut David J. Bosch - Teguh Nugroho (Jurnal Teologi (Journal of Theology), 2021)
The birth of Anabaptist movement appeared in the context of church reformation by Martin Luther in the sixteenth century in Europe.Anabaptist movement was aimed to renewing the Church according to the Scriptures, because many Protestant reformers, such as Luther and Zwingli, were not radical. They still practice some of the rules and teachings of the Roman Catholic church, such as infant baptism and maintaining the Church's relationship with the State. The Anabaptists movement rejects these practices. The Anabaptists attempted to carry out a more radical reform than their predecessors. The Anabaptist group itself has a membership of about 1.7 million worldwide. The data raises the question of how they made their mission. The facts show that the Anabaptists were persistent missionaries in preaching their Faith. The Anabaptist mission is based on three Anabaptist beliefs: Jesus became the center of faith, Mennonite who put peace and community as the center of life. These three beliefs will be analyzed using David J. Bosch's three paradigms to see the correlation between "Mission as Mediating Salvation” and the belief that Jesus is the center of faith, "Mission as Evangelism" with Mennonite beliefs that promote peace, and "Mission as Ministry by the Whole People of God” with community is the center of live. The results of this analysis will show the radicalism of the Anabaptist movement.